The Role of Teachers in Improving Competency Standards for Graduates of SMPN 129 Jakarta Students - Rosyid Rosyid; Supendi Supendi; Endang Komara; Waska Warta (Edumaspul: Jurnal Pendidikan, 2023)
National education standards are the minimum criteria that must be met in the implementation of education. national education standards include content standards, process standards, graduate competency standards, educator and education staff standards, infrastructure standards, management standards, financing standards, assessment standards. The purpose of this study is to reveal efforts to improve graduate competency standards by teachers and other parties. This research uses descriptive qualitative. The research was conducted on December 12 2022 at SMPN 129 Jakarta. The results of the study show that the KL Standards of SMPN 129 Jakarta related to Spirituality, mastery of Science and Technology, and further education can be fulfilled by the teacher's role in developing each national standard and implementing programs outside of class hours.